Oxford Textbook of Nature and Public Health : the role of nature in improving the health of a population - van den Bosch, Matilda, ....-; Bird, William, ....- (Oxford : Oxford University Press, 2018)
Human beings have always been affected by their surroundings. There are various health benefits linked to being able to access to nature; including increased physical activity, stress recovery, and the stimulation of child cognitive development. The Oxford Textbook of Nature and Public Health provides a broad and inclusive picture of the relationship between our own health and the natural environment. All aspects of this unique relationship are covered, ranging from disease prevention through physical activity in green spaces to innovative ecosystem services, such as climate change adaptation by urban trees. Potential hazardous consequences are also discussed including natural disasters, vector-borne pathogens, and allergies. This book analyses the complexity of our human interaction with nature and includes sections for example epigenetics, stress physiology, and impact assessments. These topics are all interconnected and fundamental for reaching a full understanding of the role of nature in public health and wellbeing. Much of the recent literature on environmental health has primarily described potential threats from our natural surroundings. The Oxford Textbook of Nature and Public Health instead focuses on how nature can positively impact our health and wellbeing, and how much we risk losing by destroying it. The all-inclusive approach provides a comprehensive and complete coverage of the role of nature in public health, making this textbook invaluable reading for health professionals, students, and researchers within public health, environmental health, and complementary medicine.
Keywords: Algemene ecologie; Biosociologie; Milieubescherming; Milieutechnologie